Strengthening Local Institutional Identity Through Traditional Village Management - I Gusti Ayu Purnamawati (Universitas Bumigora, 2021)
This study aims to determine the driving factors for the development of the Sepandan Pantai area in Amed Village; and the influence of the involvement of traditional village elites on strengthening the identity of local institutions. The development of research findings in the field is integrated with cultural research. The research location is in Amed Village, Abang District, Karangasem Regency. The research data consisted of primary and secondary data. Primary data collection techniques are obtained through a process of observation and direct interviews with respondents and resource persons based on interview guidelines. The data analysis technique used in this research is descriptive qualitative. Results: The embodiment of the traditional Balinese spatial concept at the Amed Beach border is expected to be able to accommodate the concepts and philosophies of Tri Hita Karana, the concepts of Tri Angga, Luan Teben, Catus Patha and Sanga Mandala, resulting in a hierarchy and spatial structure in accordance with the conceptual formulation in its implementation. The space distribution created is based on the basic output of the concept of traditional Balinese spatial patterns. Spatial orientation on the Amed coastline. Based on the cosmological arrangement of Balinese philosophy and the concept of traditional space, it gives the meaning of harmony between space and its contents, within the scope of the coastal area of ​​Amed Traditional Village.